ANALYSIS OF SALES MANAGEMENT STRATEGIES. STUDY CASE TO A DISTRIBUTION COMPANY OF BUILDING MATERIALS AND INTERIOR FURNISHING ELEMENTS HEADED IN ROMANIA - Brebeanu, Andrei Alexandru; Gurgu, Elena (Annals of Spiru Haret University. Economic Series, 2022)
This paper aims to study the sales in the field of construction materials and interior design, presenting in a case study, managerial aspects of the DedeRman SRL Company<a title="" href="file:///C:/Users/Ciotoiu/Desktop/ElaG/desktop/Cercetare%20_articole%20Gurgu%202019/Anale%20Spiru%20Haret/Issue%203_2022/Brebeanu%20_Gurgu%20E/Brebeanu%20A_Gurgu%20E_ANALYSIS%20OF%20SALES%20MANAGEMENT%20.docx#_ftn1">[1], as well as the factors that can influence the purchase decision. All these characteristics are closely related to management strategies, so its societal branch is vital to better anticipate buyers’ wishes. Thus, the company DedeRman SRL has adopted as values: seriousness, honesty, diligence, and values, that have guaranteed this company the road to success. The theme of this project was chosen because of the importance of management strategies aimed at construction materials, a vast field, which is in continuous development, being at the same time a good field to exploit. This work aims to achieve the following objectives: • Knowing the distribution of projects monitored in 2021 • Identifying the evolution of the construction materials market both internally and externally • Knowing the types of customers • Identifying the strengths and weaknesses of the DedeRman SRL company • Recognition of some communication parameters that influence the company’s management. The novelty of this topic is represented by the management analysis of the DedeRman SRL company and the construction materials market in a pandemic context. <a title="" href="file:///C:/Users/Ciotoiu/Desktop/ElaG/desktop/Cercetare%20_articole%20Gurgu%202019/Anale%20Spiru%20Haret/Issue%203_2022/Brebeanu%20_Gurgu%20E/Brebeanu%20A_Gurgu%20E_ANALYSIS%20OF%20SALES%20MANAGEMENT%20.docx#_ftnref1">[1] For data and information security reasons, the real name of the company will not be disclosed. Thank you for understanding.